Становлення екологічної безпеки як наукової дисципліни - Азаров, С.І.; Литвинов, Ю.В.; Сидоренко, В.Л. (Екологічна безпека та природокористування, 2012)
History of formation and development of ecological safety as scientific direction was considerate, such as his subject and aim.